PENERAPAN BIMBINGAN KLASIKAL DENGAN METODE BRAINSTORMING PADA KELAS XI TITL 1 DI SMK NEGERI 5 SURABAYA UNTUK MENINGKATKAN MINAT BERIBADAH - Feny Rachmayanti Anggraeni; Bambang Dibyo Wiyono; Riska Willyati Handayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education plays a very important role in the progress of the nation. The existence of education certainly aims to be able to educate the nation and for the progress of a country. This study was conducted to determine the increase in learning outcomes, which is based on the implementation of classical guidance services using the brainstorming method in class XI TITL 1 at SMK Negeri 5 Surabaya. This research method uses classroom action research. Data collection was carried out using the implementation of need assessments from class XI TITL 1 students, observation, interviews and tests. The results of the classroom action research showed that there was an increase in the learning process of students using classical guidance services on the brainstorming method. This increase can be seen by knowing the comparison between the significance value (Sig.) With a probability of 0.05, namely from the SPSS output the Sig value (2-tailed) was obtained as 0.407> 0.05, so it can be concluded that there is a difference in the average value between the Pre Test and Post Test results, which means there is an increase from the average value of the Pre Test to the post test